Serum sodium and survival benefit of liver transplantation. Issue 3 (10th February 2015) - Sharma, Pratima; Schaubel, Douglas E.; Goodrich, Nathan P.; Merion, Robert M.
Abstract : Hyponatremia is associated with elevated wait‐list mortality among end‐stage liver disease candidates for liver transplantation (LT). However, the effect of low serum sodium on the survival benefit of LT has not been examined. We sought to determine whether pretransplant hyponatremia is associated with an altered LT survival benefit. Data were obtained from the Scientific Registry of Transplant Recipients. The study population consisted of adults (age ≥ 18 years) placed on the waiting list for LT between January 1, 2005 and December 31, 2012 (n = 69, 213). The effect of hyponatremia on the survival benefit was assessed via sequential stratification, an extension of Cox regression. Each transplant recipient was matched to appropriate candidates then active on the waiting list with the same Model for End‐Stage Liver Disease (MELD) score and in the same donation service area. The focus of the analysis was the interaction between the serum sodium and the MELD score with respect to the survival benefit of LT; this was defined as the covariate‐adjusted hazard ratio contrasting post‐LT mortality and pre‐LT mortality. The LT survival benefit increased significantly with decreasing serum sodium values when the MELD scores were >11. The survival benefit of LT was not affected by serum sodium for patients with MELD scores ≤ 11. In conclusion, the LT survival benefit (or lack thereof) is independent of serum sodium for patients with MELD scores ≤ 11. The increase in the survival benefit with decreasing serum sodium among patients with MELD scores > 11 is consistent with recently approved changes to the allocation system incorporating serum sodium. Liver Transpl 21:308–313, 2015 . © 2015 AASLD.